Gambaran Profil Jaringan Lunak Wajah Menurut Holdaway Kajian terhadap pasien ortodonti Rumah Sakit Gigi dan Mulut Fakultas Kedokteran Gigi Universitas Trisakti (Penelitian) - Sherly Betris; Yuniar Zen (Fakultas Kedokteran Gigi Universitas Trisakti, 2020)
Background: The purpose of orthodontics treatment is to create the best balance among occlusal relationship, dental, and facial aesthetic, also the stability of the result. Facial profile analysis is one of proper method to precisely diagnose and decide an accurate treatment planning. Holdaway analysis considered as one of the most detailed because, Holdaway evaluate the entire facial profile. In general, malocclusion is associated with unaesthetic facial and dental appearances. So that, it becomes a main reason for patients to visit orthodontics clinic, especially to RSGM-FKG Usakti. Objective: To describe the average facial profile on orthodontics patient of RSGM-FKG Usakti using Holdaway’s method. Method: Observational research using cross sectional method to orthodontics patient of RSGM-FKG Usakti that came from January to December 2014. Eleven of Holdaway’s parameter was used as a measurement on sefalogram. The result of analytical line measurement collected in a tabulation of distribution-frequency. Result: Furthermore, The 11 measurements ; soft tissue facial angle, skeletal profile convexity, and H angle was convex. Sulcus labialis superior, lower lip to H line, and soft tissue chin thickness was ideal. Basic upper lip, upper lip strain, subnasal to H line and sulcus labialis inferior to H line was less ideal and prominence of small nose. Conclusion: The average facial profile on orthodontics patient of RSGM-FKG Usakti using Holdaway’s parameter is convex based on skeletal profile convexity and H angle.